Methods of intersectional research. Issue 1 (2nd January 2021) - Misra, Joya; Curington, Celeste Vaughan; Green, Venus Mary
Abstract: Intersectionality is a powerful concept within sociology, urging scholars to consider how an array of socially constructed dimensions of difference intersect to shape each person's experiences and actions. This paper provides a number of different blueprints for designing intersectional research, which can be adapted for different purposes. The key methodological tenets of intersectional research are oppression, relationality, complexity, context, comparison, and deconstruction. This paper defines these tenets, addresses misunderstandings of their implications, and applies these tenets to existing intersectional research. Multiple qualitative, comparative, and quantitative strategies can be used to carry out intersectional research; there is not just one way to do intersectional empirical research. While intersectional methods require thought in designing the research, they are doable. What is more, they provide much more nuanced understandings of social relations and inequality. If race, class, gender and other socially constructed dimensions of difference are understood not as static but as dynamic, researchers can employ a wide variety of methodological tools to analyze power relations via their intersections.